A new template for MRI-based intracavitary/interstitial gynecologic brachytherapy: design and clinical implementation - Villalba, Silvia Rodriguez; Sancho, Jose Richart; Palacin, Antonio Otal; Calatayud, Jose Perez; Ortega, Manuel Santos (Journal of Contemporary Brachytherapy, 2015)
Purpose : To describe the potential clinical use of a new brachytherapy applicator for gynecological tumors, with special attention to locally advanced cervical carcinoma. This device allows the combination of intracavitary radiotherapy and MRI-compatible transperineal interstitial needles. The design of this template addresses the disadvantages of currently commercially available templates: the inability of the intracavitary component to reach deep into the cervix (MUPIT), and the MRI-incompatibility of these templates (MUPIT and Syed), which necessitates use of CT imaging for the dosimetry. Material and methods : The newly developed Benidorm Template applicator allows titanium needles in a template with straight and angled holes to provide different angles of divergence to be used with currently existing MRI-compatible intrauterine tubes. It can provide total coverage of the craniocaudal and lateral extension of the tumor (intrautherus, parametrial, and paravaginal). This method is mainly indicated in advanced cervical carcinoma with bulky parametrial invasion (medial or distal), with bulky primary disease that responds poorly to external beam radiotherapy extensive paravaginal involvement (tumor thickness greater than 0.5 cm) extending to the middle or lower third of the vagina, or for disease that has invaded the bladder or rectum (stage IVA). Results : Between April 2013 until December 2014, we treated 15 patients with locally advanced cervical carcinoma employing the Benidorm Template. The median dose at D90 for the CTV was 79.8 Gy (71.5-89.9 Gy), at D 2cc for the bladder it was 77.6 Gy (69.8-90.8 Gy), and at D 2cc for the rectum it was 71.9 Gy (58.3-83.7 Gy). Values expressed in EQD2, assuming α/β of 10 for CTV and 3 for OAR. Conclusions : This new applicator allows the use of MRI-based dosimetry, thus providing the advantages of MRI volume definition. As such, it facilitates determination of complete intracavitary and interstitial CTV coverage and the sparing of normal tissues.